STUDI EKSPERIMENTAL KARAKTERISTIK NYALA API PEMBAKARAN PREMIX MINYAK KAPUK DENGAN BERBAGAI ORIENTASI MEDAN MAGNET - Dony Perdana; Dadang Gabril Setiyawan; Mochamad Choifin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
This study aims to determine the effect of the direction of magnetic fields and their absence on the premixed combustion of kapok oil on the flame's characteristics during the combustion process. Vegetable oils as a substitute for petroleum fuels are important for sustainable research. This research used a laboratory-scale experimental method to obtain the evolution, temperature, and flame height in premix combustion by adding magnets. Kapok oil is filled into boilers of 600 ml and heated to a temperature of 300 oC. A kapok oil vapor and air mixture is reacting in a burner chamber. Two permanent magnetic rods are placed on either side of the burner tip. This study found that the attraction of magnetic fields produces a brighter, slimmer flame with the highest temperature compared to the repulsive effect of magnetic fields without them. Lorentz force generated by magnetic fields continuously breaks off fuel's chemical chains, causing magnetic vibrations in flames. Oxygen-containing air around the burner is separating itself, causing electrons to be released, thus producing higher flame temperatures produced by rapid combustion reactions. A magnetic field around the flame induces a flow of air, which magnetically causes heat transfer around flames, resulting in varying flame heights.